Introducing AI in garment fault detection using YOLOv5 to reduce bottleneck - Sanjana, Jasia; Al Muhit, Abdullah; Zia, Asma (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.